Transformation of Traditional Rituals in Toraja in the Era of Modernization - Siti Khadijah; Husna Handyani; Taufik Rahman (Journal Social Humanity Perspective, 2026)
This paper examines how traditional rituals in Toraja have been transformed by modernization and how cultural practices have been maintained, negotiated, and changed in response to new social, economic, and political environments. Using a qualitative methodology of in-depth interviews, field observations, and document analysis, the study examines how rituals, especially the elaborate Rambu Solo funeral rituals have changed in the face of economic rationalization, tourism, religious influences and generational change. Results also indicate that although some elements of ritual practice are now simplified or commodified, their symbolic nature in strengthening kinship relationships and community cohesion has continued with strong force. In this case the continuity of cultural systems and their ability to respond to changes strategically and without losing their identity is demonstrated. The paper also emphasizes how management can be involved in transforming rituals, practices that are then negotiated, organized and rearranged to create a balance between authenticity and sustainability. The increasing cost of rituals and the demands of modern life push societies to create an equilibrium between the allocation of resources and tourism and globalization provide an opportunity and a threat to cultures. The generation attitudes also contribute to transformation as the young family members are more practical, yet the family is still in touch with the culture of their ancestors. Generally, the research suggests that Toraja rituals are not traditional practices but dynamic cultural resources which can be handled in such a way that can permit their further social applicability. Placing ritual transformation in wider scope of cultural management, this study helps us in comprehending how traditions may survive in times of modernization by striving to adapt to changes through adaptive governance to preserve identity and continuity.